Isolasi dan Penentuan Struktur Senyawa Golongan Steroid Dari Kulit Kayu Jawa (Lannea coromandelica) - Halimah Husain; Sudding Sudding; Hasri Hasri (Seminar Nasional LP2M UNM, 2019)
Abstract. Kayu Jawa  Plant has been widely used by the community as a medicinal plant, including as a drug for ulcers, stomach ulcers, obata wounds, shortness of breath medicine, diabetes medications, and others. Secondary metabolites of steroid from n-hexane and ethyl acetate estrogens have been found, and no steroids have been found in methanol extracts. This research will be continued with purification of Javanese bark extract and then determine the physical properties and molecular structure. The structure determination will be carried out using ultra Violet (UV) spectroscopy, mass spectroscopy, Gas Cromatography (GC) spectroscopy, and Noclear Magnetic Resonance (NMR) spectroscopy Keywords: Kayu Jawa,isolasi, identifikasi,steroid,spektroskopi,struktur molekul